Values Education Through The English Language Learning - Sugiono Sugiono (Universitas Nurul Jadid, 2022)
This study focuses on teaching values through English language learning. It explores the related literature reviewing the possibility of integrating values into the English language learning activities. Value-oriented education is an alternative to pursuing both the academic and social competence of students. It is constructed in response to the problematic issues of youngsters’ deviant behaviors and attitudes. It also challenges the trend of today’s education, which puts greater emphasis on mere academic achievement, employment opportunity, and economic growth. Consequently, students in schools turn to prioritize only academic competence for an employment chance. Few wish to achieve success both academically and socially, whereas they have a life outside their schools and homes; the life in society. The study views that integrating values into English language learning is not an easy task. It requires teachers’ innovation and creativity to pursue goals that are more than just the content of the curriculum. The challenge is that English language teachers need to construct their own lesson plans as core values are sometimes unclearly stated in the curriculum. In classrooms, the teachers recommend not to impose their own values or those of a particular culture in the society on their students